Regulatory T Cells: Regulation of Identity and Function - Grover, Payal; Goel, Peeyush N.; Greene, Mark I. (Frontiers in Immunology, 2021)
T regulatory cells suppress a variety of immune responses to self-antigens and play a role in peripheral tolerance maintenance by limiting autoimmune disorders, and other pathological immune responses such as limiting immune reactivity to oncoprotein encoded antigens. Forkhead box P3 (FOXP3) expression is required for Treg stability and affects functional activity. Mutations in the master regulator FOXP3 and related components have been linked to autoimmune diseases in humans, such as IPEX, and a scurfy-like phenotype in mice. Several lines of evidence indicate that Treg use a variety of immunosuppressive mechanisms to limit an immune response by targeting effector cells, including secretion of immunoregulatory cytokines, granzyme/perforin-mediated cell cytolysis, metabolic perturbation, directing the maturation and function of antigen-presenting cells (APC) and secretion of extracellular vesicles for the development of immunological tolerance. In this review, several regulatory mechanisms have been highlighted and discussed.